DNA polymerase activities in growing cells infected with simian virus 40. - Méchali, M (1977)
Growing CV1 cells were infected with simian virus 40 (SV40), and the levels of DNA polymerases-alpha, -beta, and -gamma were analyzed in the cytoplasm, nuclear Triton wash, and nucleus. In the cytoplasmic fraction, the amount of alpha-, beta-, or gamma-polymerase remained unaltered after SV40 infection. The activity of DNA polymerase-alpha increased five- to sixfold in the nuclear Triton wash and threefold in the nuclei and then remained enhanced only inside the nuclei. That of DNA polymerases-beta and gamma increased mostly in the nuclei after infection. These results suggest that DNA polymerase-alpha could be the major enzyme involved in SV40 DNA replication.